The Influence of Transformational Leadership on Employee Performance at PT. Toarco Jaya - Milka, Milka; Tandirerung, Ch. Jeane; Sambara, Kordiana (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2025)
Study This aiming For analyze influence leadership transformational to performance employees at PT. Toarco Jaya in North Toraja. Leadership transformational rated capable to form motivation , loyalty , and participation employee through ideal influence , motivation inspirational , stimulating intellectual , as well as individual attention . The research method used is quantitative descriptive with approach survey against 30 respondents . Data analysis techniques include Pearson correlation coefficient determination , and t-test. Research results show that leadership transformational own connection positive and significant to performance employee with mark correlation of 0.736 and the contribution influence of 54.1%. The t - value of 5.746 > t- table 2.048 with significance 0.000 < 0.05, confirms that variable leadership transformational influential significant to performance employees . Findings This show that inspiring and empowering leadership​ own role important in create environment Work productive . Therefore that , style leadership transformational recommended For adopted in the improvement strategy performance organization .